Perancangan Deteksi Cacat Pada Layer Solar Cell Menggunakan Sensor Tegangan Static Permukaan Berbasis Bluetooth - Alfanz, rocky; Muttaqin, Imamul; Carol, Juan (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2024.v23i02.P12, 2025)
This study highlights use of solar panels as a promising source of renewable energy due to the abundant availability of solar energy. However, solar cells often encounter various issues and damage, such as cracks, damage during transportation, and invisible defects that are difficult to detect. To address these issues, this research develops a defect detection tool for photovoltaic cells using a surface potential sensor connected via Bluetooth. This sensor works by detecting electrostatic field on the surface of the solar cells using a copper plate. The tool consists of several components, including an AD620 amplifier module to enhance the signal, an Arduino UNO as the microcontroller, and a Bluetooth HC-05 module to transmit data to an Android phone via Arduino Bluetooth Controller app. In testing, accuracy of the tool with a power supply input at three different distances 1mm, 3mm, and 5mm. In 1mm distance yielded better and more stable measurements, with a voltage range of 3.45V to 3.69V. In 3mm distance produced a voltage range of 3.31V to 3.54V, and the 5mm distance produced a voltage range of 2.76V to 2.99V. In testing tool under sunlight at a 1mm distance, the average voltage of normal cells was 3.534V, while voltage of damaged cells was 3.685V, indicating a difference of 0.151V. This research suggests that more cracks present in solar cells, the greater electrostatic field detected. The measurement data is then transmitted to an Android phone via Bluetooth HC-05, facilitating easier maintenance of the solar panels.